PET-SWNT nanocomposites through ultrasound assisted dissolution-evaporation - Anoop, Anand K.; Agarwal, U. S.; Nisal, Anuya; Joseph, Rani (European Polymer Journal, 2007)
Poly(ethylene terephthalate) (PET) based nanocomposites have been prepared with single walled carbon nanotubes (SWNTs) through an ultrasound assisted dissolution-evaporation method. Differential scanning calorimetry studies showed that SWNTs nucleate crystallization in PET at weight fractions as low as 0.3%, as the nanocomposite melt crystallized during cooling at temperature 24 degrees C higher than neat PET of identical molecular weight. Isothermal crystallization studies also revealed that SWNTs significantly accelerate the crystallization process. Mechanical properties of the PET-SWNT nanocomposites improved as compared to neat PET indicating the effective reinforcement provided by nanotubes in the polymer matrix. Electrical conductivity measurements on the nanocomposite films showed that SWNTs at concentrations exceeding 1 wt% in the PET matrix result in electrical percolation. Comparison of crystallization, conductivity and transmission electron microscopy studies revealed that ultrasound assisted dissolution-evaporation method enables more effective dispersion of SWNTs in the PET matrix as compared to the melt compounding method. (c) 2007 Elsevier Ltd. All rights reserved.

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid